The Englisher - Lewis, Beverly, 1949- (Minneapolis, Minn. : Bethany House, 2006)
"Annie Zook, the preacher$1 (Bs daughter, struggles to keep her promise to her father--to abandon her art for a full six months. Will Annie$1 (Bs intention to join the Amish church be derailed by the attention of a handsome Englisher?"--Provided by publisher.s
Keywords: Children of clergy -- Fiction; Women artists -- Fiction; Amish -- Fiction; English -- Pennsylvania -- Fiction; Christian fiction